HIGH-PRESSURE RAMAN SPECTROSCOPIC STUDY OF FO90 HYDROUS WADSLEYITE - Kleppe A.K.; Jephcoat A.P.; Smyth J.R. (My University, 2006)
Raman spectra of monoclinic Fo90 hydrous wadsleyite with 2.4 wt% H2O have been measured in a diamond-anvil cell with helium as a pressure-transmitting medium to 58.4 GPa at room temperature. The most intense, characteristic wadsleyite modes, the Si–O–Si symmetric stretch at 721 cm−1 and the symmetric stretch of the SiO3 unit at 918 cm−1, shift continuously to 58.4 GPa showing no evidence of a first order change in the crystal structure despite compression well beyond the stability field of wadsleyite in terms of pressure. The pressure dependence of these two modes is nearly identical for Fo90 hydrous and Fo100 anhydrous wadsleyite. A striking feature in the high-pressure Raman spectra of Fo90 hydrous wadsleyite is the appearance of new Raman modes above 9 GPa in the mid-frequency range (300–650 cm−1 at 1-bar and shifted to 500–850 cm−1 at 58.4 GPa) accompanied by a significant growth in their intensities under further compression. In the OH stretching frequency range Fo90 hydrous wadsleyite exhibits a larger number of modes than the Mg end-member phase. The higher number of modes may be due to either additional protonation sites or simply that we observe a different subset of all possible OH modes for each sample. The high-pressure behaviour of the OH stretching modes of Fo90 and Fo100 hydrous wadsleyite is consistent: OH stretching modes with frequencies <3,530 cm−1 decrease with increasing pressure whereas the higher-frequency OH modes show a close to constant pressure dependence to at least 13.2 GPa. The approximately constant pressure dependence of the OH modes above 3,530 cm−1 is consistent with protons being located at the O1···O edges around M3.
Keywords: HYDROUS WADSLEYITE; DIAMOND-ANVIL CELL; HIGH-PRESSURE; RAMAN SPECTROSCOPY; TRANSITION ZONE